Pengaruh penambahan serai wangi (Cymbopogon nardus L.) terhadap mutu teh herbal rambut jagung: Effect of lemongrass (Cymbopogon nardus L.) addition on the quality of corn silk herbal tea - Hasnah AR, Nur; Anaya, Nurul Fatya; Pato, Usman; Nopiani, Yanti; Yelmira; Juarsa, Rahmadini Payla; Kurniawan, Mhd. Andry; Parsitogi, Bintang; Rahmayani, Irma; Baihaqi (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Herbal tea is a functional drink made from a mixture of dried plants that are beneficial to the body. Corn silk has the potential to be used as herbal tea because it contains cholesterol-lowering β-sitosterol and phenol compounds as antioxidants. However, the taste is astringent and the aroma is weak, so it is necessary to add lemongrass which has a distinctive aroma and refreshing taste from essential oils. The aimed of this research was to obtain the selected ratio of corn hair and citronella to the quality characteristics of herbal tea according to SNI 3836: 2013 dry tea in packaging. This research was conducted experimentally using a completely randomized design with four treatments, namely the ratio of corn hair and citronella RS0 (100:0), RS1 (85:15), RS2 (70:30), and RS3 (55:45). The parameters observed in this research were moisture, ash, crude-fiber, polyphenol, and antioxidant activity. The antioxidant activity was measured using the DPPH method. The results showed that the RS2 treatment herbal tea with the ratio of corn hair and citronella (70:30) was the selected treatment which had a moisture of 6.25%, ash of 4.36%, crude fiber of 9.34%, polyphenol of 58.28 mg GAE/g or 5.82%, and antioxidant activity of 131.38 ppm.